Continuous infusion of physostigmine in patients with perioperative septic shock: a pharmacokinetic/pharmacodynamic study with population pharmacokinetic modeling - Pinder, Nadine; Zimmermann, Johannes B.; Gastine, Silke; Würthwein, Gudrun; Hempel, Georg; Bruckner, Thomas; Hoppe-Tichy, Torsten; Weigand, Markus A.; Swoboda, Stefanie (Biomedicine & pharmacotherapy, 2019)
BACKGROUND: In the context of the cholinergic anti-inflammatory pathway, the clinical trial Anticholium® per Se (EudraCT Number: 2012-001650-26, ClinicalTrials.gov NCT03013322) addressed the possibility of taking adjunctive physostigmine salicylate treatment in septic shock from bench to bedside. Pharmacokinetics (PK) are likely altered in critically ill patients; data on physostigmine PK and target concentrations are sparse, particularly for continuous infusion. Our objective was to build a population PK (popPK) model for physostigmine, and further evaluate pharmacodynamics (PD) and concentration-response relationship in this setting. - METHODS: In the randomized, double-blind, placebo-controlled trial, 20 patients with perioperative septic shock either received an initial dose of 0.04mg/kg physostigmine salicylate, followed by continuous infusion of 1mg/h for up to 120h, or equivalent volumes of 0.9% sodium chloride (placebo group). Physostigmine plasma concentrations and acetylcholinesterase (AChE) activity were measured; concentration-response associations were evaluated, and popPK and PD modeling was performed with NONMEM. - RESULTS: Steady state physostigmine plasma concentrations reached 7.60±2.81ng/mL (mean±standard deviation [SD]). PK was best described by a two-compartment model with linear clearance. Significant covariate effects were detected for body weight and age on clearance, as well as a high inter-individual variability of the central volume of distribution. AChE activity was significantly reduced to 30.5%-50.6% of baseline activity during physostigmine salicylate infusion. A sigmoidal direct effect PD model best described enzyme inhibition by physostigmine, with an estimated half maximal effective concentration (EC50) of 5.99ng/mL. - CONCLUSIONS: PK of physostigmine in patients with septic shock displayed substantial inter-individual variability with body weight and age influencing the clearance. Physostigmine inhibited AChE activity with a sigmoidal concentration-response effect.